Pengaruh model pembelajaran inkuiri terbimbing berbantuan media puzzle hero terhadap kemampuan berpikir kritis siswa SD Negeri 2 Sukorejo - Syafitri, Nisrina Irra; Purwanti, Kartika Yuni (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the effect of students' critical thinking skills through the application of the guided inquiry learning model assisted by the hero puzzle media. This study used a quantitative method of experimental type with a pretest-posttest control group design. The population in this study were fifth grade students at SDN 02 Sukorejo. In collecting data, this study uses test techniques, questionnaires and documentation. Data analysis techniques used the normality test, homogeneity test, and regression test. The results showed that there was an influence of the guided inquiry learning model assisted by the hero puzzle media on students' critical thinking skills. This is proven by a significance level of 0.00 <0.05, which means that Ho is rejected and Hi is accepted. So it can be concluded that the guided inquiry learning model using puzzle hero media can influence students' critical thinking skills.